The genetics of colored sequence synesthesia: Suggestive evidence of linkage to 16q and genetic heterogeneity for the condition - Tomson, Steffie N. (2011)
Synesthesia is a perceptual condition in which sensory stimulation triggers anomalous sensory experiences. In colored sequence synesthesia (CSS), color experiences are triggered by sequences such as letters or numbers. We performed a family based linkage analysis to identify genetic loci responsible for the increased neural crosstalk underlying CSS. Our results implicate a 23 MB region at 16q12.2-23.1, providing the first step in understanding the molecular basis of CSS.